Parallelism between language learning and translating - Gurdial Singh, Kulwindr Kaur (Journal of Modern Languages, 2017)
This study supports the notion put forward by Robinson (1997) that translation is actually a language learning process and the translator is always a language learner. It also attempts to match the four skills in language learning - listening, speaking. reading and writing to translation behaviour and shows that the closest to translation is writing. The paper discusses Sager’s (1994) comparison between translation and writing activities to illustrate how close both these two activities are as they involve similar approaches and features. Five experienced, non-professional, part-time translator from the University of Malaya who were the participants for this thinkÂ·aloud protocol study involving the translation of scientific texts from English to Malay were interviewed. From this study, it was found that all of them used the direct (memory, cognitive and compensation) and indirect (metacognitive, affective and social) language learning strategies proposed by Oxford (1989) and O’Malley and Chamot (1990) while translating.